Jujubaking / Siti Zulaikha Zanil Abaddin - Zanil Abaddin, Siti Zulaikha (2021)
Jujubaking is a brand name for an online bakery/dessert shop. The main objective to achieve a desired success is to offer and produce quality products from premium and affordable materials, as well as offer affordable prices by all parties. The business started on Facebook in about November, the business started with only one menu which is with the sale of brownies sold on a small scale. Then coupled with a variety of menus crafted by the founders of this business which made it have many menus and led to many requests.